The Implementation of Occupational Health and Safety (OHS) in Machining Practical Learning (MPL) - Arief Alfiyanto, Muhamad; Sukardi, Thomas; Indra, Muhammad (Universitas Pendidikan Ganesha, 2023)
Occupational Safety and Health (K3) is essential in machining engineering lessons at vocational schools because students often carry out practices involving many complex and sharp objects. This research aims to analyze occupational safety and health implementation in machining practical learning. This research uses an ex-post facto quantitative approach—research subjects in class XI machining engineering in four vocational schools with a sample of 172 people. Data collection uses surveys, observations, interviews, questionnaires, and documentation. The data analysis technique in this research is regression analysis. The findings show first, there is a significant influence between the application of K3 on learning machining practices. Second, the analysis results of the impact of the application of K3 on learning machining practices are in the weak category. Third, the results of the synthesis and evaluation show that there are four reasons or factors that influence the inadequate implementation of K3 in learning machining practices, including the lack of student knowledge about K3, the lack of school facilities related to K3, the lack of student perception regarding the importance of K3, and the lack of student behavior regarding K3 (motivation, discipline, honesty). This research concludes that applying K3 in learning machining practices is the task of stakeholders and every individual because health and safety at work are some of the supporting aspects towards success.